Complete genomic analysis of ST117 lineage extraintestinal pathogenic Escherichia coli (ExPEC) to reveal multiple genetic determinants to drive its global transmission: ST117 E. coli as an emerging multidrug‐resistant foodborne ExPEC with zoonotic potential. Issue 6 (18th August 2022) - Xia, Fufang; Jiang, Min; Wen, Zhe; Wang, Zhongxing; Wang, Min; Xu, Yudian; Zhuge, Xiangkai; Dai, Jianjun
Abstract: Avian pathogenic Escherichia coli (APEC) is recognized as a primary source of foodborne extraintestinal pathogenic E . coli (ExPEC), which poses a significant risk of extraintestinal infections in humans. The potential of human infection with ST117 lineage APEC/ExPEC from poultry is particularly concerning. However, relatively few whole‐genome studies have focused on ST117 as an emerging ExPEC lineage. In this study, the complete genomes of 11 avian ST117 isolates and the draft genomes of 20 ST117 isolates in China were sequenced to reveal the genomic islands and large plasmid composition of ST117 APEC. With reference to the extensive E. coli genomes available in public databases, large‐scale comprehensive genomic analysis of the ST117 lineage APEC/ExPEC was performed to reveal the features of the ST117 pan‐genome and population. The high variability of the accessory genome emphasized the diversity and dynamic traits of the ST117 pan‐genome. ST117 isolates recovered from different hosts and geographic sources were randomly located on a phylogeny tree, suggesting that ST117 E. coli lacked host specificity. A time‐scaled phylogeny tree showed that ST117 was a recent E. coli lineage with a relatively short evolutionary period. Further characterization of a wide diversity of ExPEC‐related virulence genes, pathogenicity islands (PAIs), and resistance genes of the ST117 pan‐genome provided insights into the virulence and resistance of ST117 APEC/ExPEC. The results suggested zoonotic potential of ST117 APEC/ExPEC between birds and humans. Moreover, genomic analysis showed that a pool of diverse plasmids drove the virulence and multidrug resistance of ST117 APEC/ExPEC. Several types of large plasmids were scattered across the ST117 isolates, but there was no strong plasmid‐clade adaptation. Combined with the pan‐genome analysis, a double polymerase chain reaction (PCR) method was designed for rapid and cost‐effective detection of ST117 isolates from various avian and human APEC/ExPEC isolates. Overall, this study addressed a gap in current knowledge about the ST117 APEC/ExPEC genome, with significant implications to understand the success and spread of ST117 APEC/ExPEC.